Solid-state battery negative electrode buffer layer and preparation method and application thereof
By introducing a negative electrode buffer layer composed of polymer and functional filler between the negative electrode of the solid-state battery and the solid electrolyte, the problems of poor interface contact and poor mechanical stability are solved, and efficient ion conduction and battery performance are achieved.
Patent Information
- Application Number
- CN202510477129.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2025-07-04
AI Technical Summary
The interface contact between the negative electrode of existing solid-state batteries and the solid electrolyte is poor, poor mechanical stability, ion conduction path obstruction and the risk of failure of conductive interface materials, resulting in increased internal resistance of the battery and degraded circulation performance.
A negative electrode buffer layer is used, which contains 60 to 80% of the polymer substrate material and 20 to 40% of the functional fillers, such as inorganic ion conductors, conductive carbon materials and nanooxides, and is formed on the surface of the negative electrode by coating or spraying the film to expand the volume of the negative electrode, thereby improving the interface bonding strength and ionic conductivity.
It significantly improves interface stability and ionic conductivity, reduces interface impedance, enhances the cycling stability and energy density of the battery, and extends the battery life.
Smart Images

Figure BDA0005361670480000101 
Figure HDA0005361670490000011 
Figure HDA0005361670490000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of batteries, and particularly relates to a negative electrode buffer layer for a solid-state battery, a preparation method thereof, and an application thereof. Background Art
[0002] In the design of the negative electrode structure of a solid-state battery, the negative electrode material is usually directly contacted with the solid electrolyte, or a conductive interface material is introduced between the negative electrode and the solid electrolyte to improve the interface conduction performance. Such conductive interface materials are mostly coating layers of metal (such as lithium, nickel, etc.) conductive materials or polymer binders. These conductive interface materials have the following disadvantages: (1) Poor interface contact: Due to the microscopic unevenness and expansion stress between the solid electrolyte and the negative electrode material, the interface contact is not tight, affecting the ion conduction performance; (2) Poor mechanical stability: The negative electrode material expands and contracts during charge and discharge, easily causing cracking of the conductive interface material, resulting in an increase in the internal resistance of the battery and a decrease in the cycle performance; (3) Obstruction of the ion conduction path: Existing conductive interface materials are difficult to balance the functions of high conductivity and stress buffering between the negative electrode and the solid electrolyte, and cannot effectively reduce the interface impedance; (4) Risk of failure of the conductive interface material: Metal or binder coatings may undergo chemical reactions or interface detachment during long-term cycling, resulting in battery failure. Summary of the Invention
[0003] In order to overcome at least one of the above-mentioned technical problems existing in the prior art, one of the purposes of the present invention is to provide a negative electrode buffer layer.
[0004] Another purpose of the present invention is to provide a preparation method of the negative electrode buffer layer.
[0005] Another purpose of the present invention is to provide a solid-state battery.
[0006] Another purpose of the present invention is to provide an application of the above-mentioned negative electrode buffer layer in the field of batteries.
[0007] In order to achieve the above purposes, the technical solutions adopted by the present invention are as follows:
[0008] The first aspect of the present invention provides a negative electrode buffer layer, which includes a base material with a mass percentage of 60-80% and a functional filler with a mass percentage of 20-40%;
[0009] The base material includes a polymer;
[0010] The functional filler includes at least one of an inorganic ion conductor, a conductive carbon material, and a nano-oxide.
[0011] The negative electrode buffer layer in the present invention contains a highly elastic polymer material and functional fillers. The highly elastic polymer material can effectively buffer the volume expansion of the negative electrode in the present invention, prevent interface cracking and delamination, and can significantly improve the ionic conductivity, making the buffer layer have high electrical conductivity and reducing the interface impedance; the functional fillers are used to enhance the mechanical strength and interface stability of the buffer layer in the present invention. The negative electrode buffer layer in the present invention can effectively fill the microscopic voids between the negative electrode and the solid electrolyte, improve the bonding interface, on the one hand, avoid problems such as interface shedding and interface cracking caused by the expansion of the negative electrode, and on the other hand, improve the interface contact quality between the negative electrode and the solid electrolyte and reduce the interface impedance.
[0012] The negative electrode buffer layer in the present invention has high mechanical strength, especially high tensile strength and flexibility, and at the same time has high ionic conductivity and high density, which can significantly improve the interface bonding quality and enhance the cycle stability of the battery.
[0013] In some embodiments of the present invention, the polymer includes at least one of polyvinylidene fluoride (i.e., PVDF), polyethylene oxide (i.e., PEO), polyurethane (i.e., PU), and polyacrylonitrile (i.e., PAN). The polymers used in the present invention have the following advantages: (a) excellent chemical stability: the polymers adopted in the present invention are resistant to electrolyte corrosion and can extend the battery cycle life; (b) relatively high mechanical strength: the polymers adopted in the present invention have a high elastic modulus (its elastic modulus is 0.1-2 GPa), which can inhibit interface delamination and improve the density of the buffer layer; (c) easy to process: the polymers adopted in the present invention are easily soluble in common solvents such as N-methylpyrrolidone, which is convenient for film-forming processes (such as spraying, casting, etc.). The polyethylene oxide (i.e., PEO) in the present invention is compounded with functional fillers (for example: nano-oxides, which can inhibit the crystallization phenomenon of PEO) when used to improve the elasticity of the negative electrode buffer layer. PVDF and PAN can play a good buffering role when compounded with inorganic ion conductors or nano-oxides during use.
[0014] In some embodiments of the present invention, the elastic modulus of the polymer is 0.1-2 GPa.
[0015] In some embodiments of the present invention, the elongation at break of the polymer is ≥300%.
[0016] In some embodiments of the present invention, the weight-average molecular weight of the polymer is 50,000 to 1.2 million.
[0017] In some embodiments of the present invention, the inorganic ion conductor includes at least one of lithium lanthanum zirconium oxide, lithium titanium oxide, Li3PS4, lithium germanium phosphorus sulfide compound, lithium aluminum titanium phosphate, and lithium aluminum germanium phosphate.
[0018] In some embodiments of the present invention, the conductive carbon material is selected from at least one of graphene, carbon nanotubes, acetylene black, carbon fiber, carbon black, graphite, carbon aerogel, and carbon quantum dots.
[0019] In some embodiments of the present invention, the nano-oxide is selected from at least one of nano-Al2O3, nano-ZrO2, nano-titanium dioxide, nano-zinc oxide, nano-iron oxide, and nano-silica.
[0020] In some embodiments of the present invention, the particle size of the functional filler is ≤ 1 μm.
[0021] In some embodiments of the present invention, the conductivity of the functional filler is ≥ 1×10 -4 S / cm.
[0022] In some embodiments of the present invention, the specific surface area of the functional filler is ≥ 10 m 2 / g.
[0023] In some embodiments of the present invention, the thickness of the negative electrode buffer layer is 1 - 10 μm.
[0024] In some embodiments of the present invention, the polymer and the functional filler are connected by at least one selected from physical entanglement, chemical bond, and π-π interaction.
[0025] In some embodiments of the present invention, a second aspect of the present invention provides a method for preparing the negative electrode buffer layer described in the first aspect of the present invention, including the following steps:
[0026] A raw material including a substrate material and a functional filler is made into a slurry, and then the slurry is formed into a film to obtain the negative electrode buffer layer.
[0027] In some embodiments of the present invention, the step of forming the slurry into a film is: making the slurry form a film on the surface of the negative electrode by coating or spraying.
[0028] The negative electrode buffer layer in the present invention is directly formed into a film on the surface of the negative electrode, has a high bonding strength with the negative electrode, and has long-term stability.
[0029] In some embodiments of the present invention, the slurry further contains a solvent, and the solvent includes at least one of N-methylpyrrolidone, ethanol, acetone, and isopropyl alcohol.
[0030] A third aspect of the present invention provides a solid-state battery, including a positive electrode, a solid electrolyte, and a negative electrode. The solid-state battery further includes the negative electrode buffer layer described in the first aspect of the present invention; the negative electrode buffer layer is located between the negative electrode and the solid electrolyte.
[0031] The fourth aspect of the present invention provides an application of the negative electrode buffer layer described in the first aspect of the present invention in a battery.
[0032] The beneficial effects of the present invention are as follows: The negative electrode buffer layer in the present invention includes a polymer base material, which has high elasticity and can buffer problems such as interface detachment and interface cracking caused by the volume expansion of the negative electrode. Moreover, it has a high ionic conductivity (about 6×10 -4 S / cm to 1.2×10 -3 S / cm), a high tensile strength (10.5 - 16 MPa), excellent flexibility, and significantly improves the interface stability, ionic conductivity, and mechanical strength.
[0033] By introducing an electrode buffer layer in the battery of the present invention, it can effectively buffer the volume expansion of the negative electrode, prevent interface cracking and delamination, can effectively fill the microscopic voids between the negative electrode and the solid electrolyte, improve the bonding interface, and thus has a low interface impedance (18 - 30 Ω·cm 2 ), a high energy density (290 - 320 Wh / kg), and a high Coulomb efficiency (98.8% - 99.5%). The capacity retention rate after 500 cycles is as high as 92%, and it has excellent battery performance. By introducing a negative electrode buffer layer in the battery, the present invention can enhance the mechanical stability of the interface between the negative electrode and the electrolyte, reduce the increase in internal resistance during the battery cycle, extend the battery life, and improve the energy density and rate performance of the battery. Description of the Drawings
[0034] Figure 1 It is a schematic structural diagram of the solid-state battery in Example 4.
[0035] Figure 2 It is a scanning electron microscope image of the negative electrode buffer layer in Example 1 before cycling.
[0036] Figure 3 It is a scanning electron microscope image of the negative electrode buffer layer in Example 1 after 1000 cycles.
[0037] Figure 4 It is a scanning electron microscope image of the negative electrode buffer layer in Comparative Example 1 after 200 cycles.
[0038] Reference Signs:
[0039] Aluminum foil current collector 1, positive electrode 2, electrolyte layer 3, buffer layer 4, negative electrode 5, copper foil current collector 6. Detailed Embodiments
[0040] The following further describes the specific implementation of the present invention in conjunction with the accompanying drawings and examples. However, the implementation and protection of the present invention are not limited thereto. It should be noted that for the processes not specifically described in detail below, those skilled in the art can implement or understand them with reference to the prior art. Reagents or instruments without indicating the manufacturer can be obtained as conventional products through commercial purchase.
[0041] In some embodiments of the present invention, a negative electrode buffer layer is provided, which includes a base material with a mass percentage of 60 - 80% and a functional filler with a mass percentage of 20 - 40%.
[0042] The base material includes a polymer.
[0043] The functional filler includes at least one of an inorganic ion conductor, a conductive carbon material, and a nano - oxide.
[0044] In some embodiments of the present invention, a negative electrode buffer layer is provided, which is composed of a base material with a mass percentage of 60 - 80% and a functional filler with a mass percentage of 20 - 40%.
[0045] The base material includes a polymer.
[0046] The functional filler includes at least one of an inorganic ion conductor, a conductive carbon material, and a nano - oxide.
[0047] In some embodiments of the present invention, the mass percentage of the base material can be any value among 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80% or any range formed by any two of them.
[0048] In some embodiments of the present invention, the elastic modulus of the polymer is 0.1 - 2 GPa. When the elastic modulus of the polymer is within this range, it can balance the supportability and flexibility. In some embodiments of the present invention, the elastic modulus of the polymer is any value among 0.1 GPa, 0.2 GPa, 0.3 GPa, 0.4 GPa, 0.5 GPa, 0.6 GPa, 0.7 GPa, 0.8 GPa, 0.9 GPa, 1 GPa, 1.1 GPa, 1.2 GPa, 1.3 GPa, 1.4 GPa, 1.5 GPa, 1.6 GPa, 1.7 GPa, 1.8 GPa, 1.9 GPa, 2 GPa or any range formed by any two of them.
[0049] In some embodiments of the present invention, the elongation at break of the polymer is ≥300% to ensure that the negative electrode buffer layer containing the polymer can effectively adapt to the repeated expansion / shrinkage of the volume of the negative electrode (for example, the expansion rate of a silicon negative electrode is about 300%). In some embodiments of the present invention, the elongation at break of the polymer is 300% to 1000%. In some embodiments of the present invention, the elongation at break of the polymer is any value among 300%, 400%, 500%, 600%, 700%, 800%, 900%, 1000% or a range value formed by any two of them.
[0050] In some embodiments of the present invention, the weight-average molecular weight of the polymer is 50,000 to 1,200,000; in some embodiments of the present invention, the weight-average molecular weight of the polymer is any value among 50,000, 100,000, 150,000, 200,000, 250,000, 300,000, 350,000, 400,000, 450,000, 500,000, 550,000, 600,000, 650,000, 700,000, 750,000, 800,000, 850,000, 900,000, 950,000, 1,000,000, 1,050,000, 1,100,000, 1,150,000, 1,200,000 or a range value formed by any two of them.
[0051] In some embodiments of the present invention, the polymer contains polar groups, such as: the C-F bond of PVDF, the ether oxygen bond of PEO, the urethane bond of PU, etc., and these polar groups can enhance the interfacial bonding with the functional filler.
[0052] In some embodiments of the present invention, the conductivity of the functional filler is ≥1×10 -4 S / cm; in some embodiments of the present invention, the conductivity of the functional filler is 1×10 -4 S / cm to 1200 S / cm.
[0053] In some embodiments of the present invention, the specific surface area of the functional filler is ≥10 m 2 / g; in some embodiments of the present invention, the specific surface area of the functional filler is 10 to 3000 m 2 / g; in some embodiments of the present invention, the specific surface area of the functional filler is 10 m 2 / g, 50 m 2 / g, 100 m 2 / g, 200 m 2 / g, 300 m 2 / g, 400 m 2 / g, 500 m 2 / g, 600 m 2 / g, 700 m 2 / g, 800 m 2 / g, 900 m 2 / g, 1000 m 2 / g, 1100 m 2 / g, 1200 m 2 / g, 1300 m 2 / g, 1400 m 2 / g, 1500 m 2 / g, 1600 m 2 / g, 1700 m 2 / g, 1800 m 2 / g, 1900 m 2 / g, 2000 m 2 / g, 2100 m 2 / g, 2200 m 2 / g, 2300 m 2 / g, 2400 m 2 / g, 2500 m 2 / g, 2600 m 2 / g, 2700 m 2 / g, 2800 m 2 / g, 2900 m 2 / g, 3000 m 2 Any value in / g or the range value formed by any two of them.
[0054] In some embodiments of the present invention, the mass percentage of the functional filler can be any value in 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40% or the range value formed by any two of them.
[0055] In some embodiments of the present invention, the particle size of the functional filler ≤ 1 μm to ensure that the functional filler can be uniformly dispersed in the polymer matrix and avoid stress concentration. If the particle size of the functional filler is too large, it will lead to a reduction in the interfacial contact area and affect ion / electron transport.
[0056] In some embodiments of the present invention, the polymer and the functional filler are connected by at least one selected from physical entanglement, chemical bond, and π-π interaction.
[0057] In some embodiments of the present invention, the polymer includes at least one of polyvinylidene fluoride, polyethylene oxide, polyurethane, and polyacrylonitrile.
[0058] In some embodiments of the present invention, the weight-average molecular weight of polyvinylidene fluoride (PVDF) is 500,000 - 1,200,000.
[0059] In some embodiments of the present invention, the molecular weight of polyethylene oxide (PEO) is 100,000 - 500,000.
[0060] In some embodiments of the present invention, the molecular weight of the polyurethane (PU) prepolymer is 50,000 to 200,000.
[0061] In some embodiments of the present invention, the inorganic ion conductor includes at least one of lithium lanthanum zirconium oxide, lithium titanium oxide, Li3PS4, lithium germanium phosphorus sulfide compound, lithium aluminum titanium phosphate, and lithium aluminum germanium phosphate.
[0062] In some embodiments of the present invention, the particle size of the inorganic ion conductor is ≤1 μm.
[0063] In some embodiments of the present invention, the specific surface area of the inorganic ion conductor is ≥10 m 2 / g.
[0064] In some embodiments of the present invention, the conductive carbon material is selected from at least one of graphene, carbon nanotubes, acetylene black, carbon fiber, carbon black, graphite, carbon aerogel, and carbon quantum dots.
[0065] In some embodiments of the present invention, the conductivity of graphene is about 10 3 S / cm.
[0066] In some embodiments of the present invention, the nano-oxide is selected from at least one of nano-Al2O3, nano-ZrO2, nano-titanium dioxide, nano-zinc oxide, nano-iron oxide, and nano-silicon dioxide.
[0067] In some embodiments of the present invention, the particle size of the nano-oxide is ≤100 nm. Nano-scale fillers (such as nano-oxides) can enhance the interfacial mechanical interlock with the polymer matrix, inhibit crack propagation, and thus improve the mechanical strength of the negative electrode buffer layer.
[0068] In some embodiments of the present invention, the specific surface area of the nano-oxide is ≥50 m 2 / g.
[0069] In some embodiments of the present invention, the thickness of the negative electrode buffer layer is 1 to 10 μm; in some embodiments of the present invention, the thickness of the negative electrode buffer layer is any value among 1 μm, 2 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm or any range value formed by any two of them.
[0070] In some embodiments of the present invention, the present invention provides a method for preparing the above-mentioned negative electrode buffer layer, including the following steps:
[0071] A slurry is made from raw materials including a substrate material and functional fillers, and then the slurry is formed into a film to obtain the negative electrode buffer layer.
[0072] In some embodiments of the present invention, the slurry further contains a solvent, and the solvent includes at least one of N-methylpyrrolidone, ethanol, acetone, and isopropanol.
[0073] In some embodiments of the present invention, the present invention provides a solid-state battery, including a positive electrode, a solid electrolyte, and a negative electrode. The solid-state battery further includes the above-mentioned negative electrode buffer layer; the negative electrode buffer layer is located between the negative electrode and the solid electrolyte.
[0074] In some embodiments of the present invention, the solid-state battery can be a solid-state lithium-ion battery, a solid-state sodium-ion battery, or a solid-state potassium-ion battery.
[0075] In some embodiments of the present invention, the material of the positive electrode is selected from at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide.
[0076] In some embodiments of the present invention, the material of the positive electrode is selected from at least one of sodium nickel manganese oxide, sodium iron phosphate, and Prussian blue.
[0077] In some embodiments of the present invention, the material of the negative electrode is selected from at least one of graphite, hard carbon, sodium titanate, silicon-carbon composite material, lithium titanate, lithium metal, and silicon.
[0078] In some embodiments of the present invention, the solid electrolyte is selected from at least one of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate, lithium phosphorus sulfur compound, lithium germanium phosphorus sulfur compound, polyethylene oxide, and polyvinylidene fluoride.
[0079] The following further describes the specific implementation of the present invention in detail with specific embodiments:
[0080] Example 1
[0081] This example provides a negative electrode buffer layer, which is composed of 70% by mass of polyvinylidene fluoride (PVDF) and 30% by mass of LLZO. LLZO is Li7La3Zr2O 12 , the thickness of this buffer layer is 5 μm and it is located on the surface of the negative electrode. PVDF: molecular weight 8 million, elastic modulus: 1.5 GPa, elongation at break: 400%, density is 1.78 g / cm 3 , glass transition temperature is -40 °C; LLZO (Li7La3Zr2O 12 ): particle size is 200 - 500 nm, specific surface area of LLZO (functional filler) is 25 m 2 / g, purity ≥ 99.9%, ionic conductivity measured at room temperature ≥ 1 × 10-3 S / cm.
[0082] The negative electrode buffer layer in this example is prepared by the following preparation method, and the specific steps are:
[0083] (1) Dissolve PVDF in N-methylpyrrolidone (NMP) solvent. The mass ratio of PVDF to NMP is 1:9 (i.e., 10% solid content). The dissolution temperature is 60°C, and the stirring time is 6 hours to form a homogeneous solution.
[0084] (2) Then add LLZO powder to the homogeneous solution prepared in step (1) and perform ultrasonic dispersion. Ultrasonic frequency: 40 kHz; ultrasonic time: 2 hours; power: 200 W to obtain a mixed slurry.
[0085] (3) Coating the mixed slurry prepared in step (2) on the surface of the negative electrode by spraying method. The material of the negative electrode is silicon-carbon composite material (Si / C, silicon content 10 - 20%, particle size 5 - 10 μm); coating thickness: 5 μm, spraying pressure 0.2 MPa, nozzle diameter 0.3 mm, and then drying in vacuum at 80°C for 12 hours to obtain the negative electrode buffer layer in this example.
[0086] Example 2
[0087] This example provides a negative electrode buffer layer, which is composed of 65% by mass of polyethylene oxide (PEO) and 35% by mass of graphene. PEO: molecular weight 300,000 (purchased from Sigma-Aldrich), elastic modulus of PEO: 0.8 GPa. Elongation at break of PEO: 500%, melting point 65°C, purity ≥ 99%; graphene: monolayer rate ≥ 95%, sheet diameter 1 μm, specific surface area ≥ 2630 m 2 / g (purchased from XG Sciences), conductivity of graphene (functional filler): 1200 S / cm. The thickness of the negative electrode buffer layer in this example is 3 μm and is located on the surface of the negative electrode.
[0088] The negative electrode buffer layer in this example is prepared by the following method. The specific steps are as follows:
[0089] (1) Ball-mill and mix PEO and graphene in ethanol for 4 hours. Ball-mill rotation speed: 300 rpm;
[0090] The material of the grinding balls: zirconia balls, diameter 3 mm; ball-to-material ratio: 5:1. After ball-milling, remove the grinding balls to obtain a mixed slurry; the amount of ethanol used is 50% of the total mass of the mixed slurry.
[0091] (2) Use the spin-coating method to form a film of the mixed slurry in step (1) on the surface of the negative electrode. Spin-coating rate: 2000 rpm, time 30 seconds; after spin-coating, perform annealing treatment at 60°C for 6 hours to obtain the negative electrode buffer layer in this example.
[0092] Example 3
[0093] This example provides a negative electrode buffer layer, which is composed of 75% by mass of polyurethane (PU) and 25% by mass of lithium titanate (LTO, Li4Ti5O 12 ), and the thickness of this buffer layer is 8 μm and it is located on the surface of the negative electrode. Elongation at break of PU: 450%; Lithium titanate (Li4Ti5O 12 ): particle size 500 nm - 1 μm, purity ≥ 99.5%, conductivity of LTO (functional filler): 1×10 -4 S / cm, specific surface area 20 m 2 / g.
[0094] The negative electrode buffer layer in this example is prepared by the following method, and the specific steps are as follows:
[0095] (1) Mix the PU prepolymer with the LTO powder, and then add a curing agent to obtain a mixed slurry; Curing agent: hexamethylene diisocyanate (HDI), PU prepolymer:curing agent = 100:5 (mass ratio); PU prepolymer: polyether-type PU (purchased from BASF ), molecular weight 150,000, elastic modulus 1.2 GPa.
[0096] (2) Coat the mixed slurry from step (1) on the surface of the negative electrode, and then cure it at 80 °C for 2 hours to obtain the negative electrode buffer layer in this example.
[0097] Example 4
[0098] As Figure 1 shown, this example provides a solid-state battery, which is composed of an aluminum foil current collector 1, a positive electrode 2, an electrolyte layer 3, a buffer layer 4, a negative electrode 5, and a copper foil current collector 6 stacked in sequence. The buffer layer 4 can use the negative electrode buffer layer in Example 1, Example 2, or Example 3. Among them, positive electrode material: lithium nickel cobalt manganate (NCM811); negative electrode material: graphite (specific surface area 3 m 2 / g); solid-state electrolyte: lithium lanthanum zirconium oxide (LLZO, thickness 20 μm); battery structure: Al / NCM811 / LLZO / buffer layer / graphite / Cu foil.
[0099] Comparative Example 1
[0100] This example provides a negative electrode buffer layer, the material of this buffer layer is PVDF, the thickness is 8 μm, and it is located on the surface of the negative electrode.
[0101] The negative electrode buffer layer in this example is prepared by the following method, and the specific steps are as follows:
[0102] (1) Dissolve PVDF in an N-methylpyrrolidone (NMP) solvent, and the mass ratio of PVDF to NMP is 1:9; dissolution temperature 60 °C, stirring time 6 hours, to form a homogeneous solution;
[0103] (2) Coating the homogeneous solution prepared in step (1) on the surface of the negative electrode by spraying method, and drying it in vacuum at 80 °C for 12 hours to obtain the negative electrode buffer layer in this example. Among them, the coating thickness is 8 μm, the spraying pressure is 0.2 MPa, and the nozzle diameter is 0.3 mm.
[0104] Comparative Example 2
[0105] This example provides a negative electrode buffer layer, which is composed of 90% by mass of polyvinylidene fluoride (PVDF) and 10% by mass of LLZO. LLZO is Li7La3Zr2O 12 , and the thickness of this buffer layer is 5 μm and it is located on the surface of the negative electrode.
[0106] The negative electrode buffer layer in this example is prepared by the following preparation method. The specific steps are as follows:
[0107] (1) Dissolve PVDF in N-methylpyrrolidone (NMP) solvent, and the mass ratio of PVDF to NMP is 1:9; the dissolution temperature is 60 °C, and the stirring time is 6 hours to form a homogeneous solution;
[0108] (2) Then add LLZO powder to the homogeneous solution prepared in step (1), and ultrasonically disperse it for 2 hours. Ultrasonic frequency: 40 kHz; ultrasonic time: 2 hours; power: 200 W to obtain a mixed slurry;
[0109] (3) Coating the mixed slurry prepared in step (2) on the surface of the negative electrode by spraying method, and drying it in vacuum at 80 °C for 12 hours to obtain the negative electrode buffer layer in this example. Among them, the coating thickness is 5 μm, the spraying pressure is 0.2 MPa, and the nozzle diameter is 0.3 mm.
[0110] Comparative Example 3
[0111] This example provides a negative electrode buffer layer, which is composed of 70% by mass of polyvinylidene fluoride (PVDF) and 30% by mass of nano-copper particles. Nano-copper particle size: 50 - 100 nm; the thickness of this buffer layer is 5 μm and it is located on the surface of the negative electrode.
[0112] The negative electrode buffer layer in this example is prepared by the following preparation method. The specific steps are as follows:
[0113] (1) Dissolve PVDF in N-methylpyrrolidone (NMP) solvent, and the mass ratio of PVDF to NMP is 1:9; the dissolution temperature is 60 °C, and the stirring time is 6 hours to form a homogeneous solution;
[0114] (2) Then, add nano - copper particles to the homogeneous solution prepared in step (1), and ultrasonically disperse for 2 hours. Ultrasonic frequency: 40 kHz; Ultrasonic time: 2 hours; Power: 200 W to obtain a mixed slurry;
[0115] (3) Coat the mixed slurry prepared in step (2) on the surface of the negative electrode by spraying method, and vacuum - dry at 80 °C for 12 hours to prepare the negative - electrode buffer layer in this example. Among them, the coating thickness is 5 μm, the spraying pressure is 0.2 MPa, and the nozzle diameter is 0.3 mm.
[0116] Performance test:
[0117] Conduct peel tests on the negative - electrode buffer layers prepared in Examples 1 - 3 and Comparative Examples 1 - 3 respectively. Sample size: Cut the electrode into strip - shaped samples with a width of 10 mm and a length of 100 mm. Pretreatment: Let it stand for 24 hours in a constant - temperature and constant - humidity environment (such as 25 °C, 50% RH) to ensure the stability of the material state. Use double - sided tape to fix the uncoated current - collector end on the glass plate, and separate the coated end from the substrate to form a peelable free end. Use an Instron universal material testing machine equipped with a high - precision force sensor. Customized clamps ensure that the sample maintains a fixed peel angle (90°) during the test. Tensile speed: 100 mm / min, and record the force value in the stable peel section. Repeat the test on at least 5 samples and take the average value to reduce errors. The specific test results are shown in Table 1 below.
[0118] Table 1 Peel - force test results of the negative - electrode buffer layers in Examples 1 - 3 and Comparative Examples 1 - 3
[0119] Test group Peeling strength (N / cm) Test group Peeling strength (N / cm) Example 1 2.5 Comparative example 1 0.8 Example 2 1.9 Comparative example 2 1.2 Example 3 2.3 Comparative example 3 0.6
[0120] As can be seen from Table 1, the negative electrode buffer layer in Example 1 contains PVDF and LLZO. PVDF provides a rigid skeleton, and LLZO nanoparticles are combined with PVDF through hydrogen bonds to form a dense interface, significantly improving the binding force. The negative electrode buffer layer in Example 2 contains PEO and graphene. The π-π interaction between the flexible segments of PEO and graphene enhances the adhesion, but the high crystallinity of PEO results in a weaker interface binding than that in Example 1. The negative electrode buffer layer in Example 3 contains PU and LTO. The high elasticity of PU (elongation at break > 300%) is anchored to LTO particles through physical entanglement to form an "elastic-rigid" interlocking structure, thus having a strong binding force. In Comparative Example 1, the negative electrode buffer layer uses pure PVDF. PVDF has high rigidity and lacks functional fillers, and the interface is prone to cracking due to stress concentration, resulting in a significant reduction in the binding force. In Comparative Example 2, the negative electrode buffer layer uses PVDF with a mass percentage of 90% and LLZO with a mass percentage of 10%. The content of LLZO is insufficient to form a continuous conductive network. Although the interface binding force is higher than that in Comparative Example 1, it is still weak. In Comparative Example 3, the negative electrode buffer layer uses PVDF and nano-copper. The polarity difference between nano-copper and PVDF is large, and the interface compatibility is poor. Moreover, copper is oxidized to form an insulating layer (CuO), further weakening the binding force.
[0121] The negative electrode buffer layers prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to a bending test. Test equipment: A dynamic bending test machine (such as Instron ElectroPuls E3000) was used. The fixture spacing was set to 20 mm, the bending amplitude was 90°, the temperature was 25 ± 2 °C, and the relative humidity was 50 ± 5%. Environmental factors were avoided from interfering with the material properties. Termination condition: When visible cracks appeared on the surface of the specimen or the conductivity decreased by more than 10%, the test was terminated and the number of bending times was recorded. The number of times when the crack phenomenon first appeared was also recorded. The specific test results are shown in Table 2 below.
[0122] The tensile strengths of the negative electrode buffer layers prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested respectively according to the test method described in ASTM D638 standard. The sample size was Type V, and the tensile rate was 10 mm / min. The specific test results are shown in Table 2 below.
[0123] The impedance spectra of the negative electrode buffer layers prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested by electrochemical impedance spectroscopy (EIS) method, and then the ionic conductivity was tested. The test frequency range was 0.1 Hz to 1 MHz, and the test was carried out according to the test method described in IEEE 1657 standard. The ionic conductivity and the interface impedance data on the interface side of the battery negative electrode obtained by the test are shown in Table 2 below.
[0124] The negative electrode buffer layers prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were assembled into batteries. The difference in the battery structure from that of Example 4 was only the buffer layer. Then, the batteries were cycled 500 times at a charge-discharge rate of 0.5C and a voltage range of 2.5 - 4.2V. Then, the energy density, Coulomb efficiency, and capacity retention rate after cycling of the batteries were tested with reference to the test method described in the standard GB / T18287-2013. The specific test results are shown in Table 2 below.
[0125] Table 2 Performance data of the negative electrode buffer layers in Examples 1 to 3 and Comparative Examples 1 to 3
[0126]
[0127] As can be seen from Table 2, compared with Comparative Examples 1 to 3, the negative electrode buffer layers in Examples 1 to 3 of the present invention have higher ionic conductivity and tensile strength, excellent flexibility, and significantly improve the interfacial stability and ionic conductivity. The batteries assembled with the negative electrode buffer layers in the present invention have lower interfacial impedance, higher energy density, and Coulomb efficiency, and the capacity retention rate after 500 cycles is as high as 85%. They have excellent battery performance, especially significantly superior to Comparative Examples 1 to 3 in terms of cycle life, interfacial impedance, and energy density. The negative electrode buffer layer of Comparative Example 3 uses nano-copper and PVDF, and it is prone to failure during cycling. Its failure mechanism is as follows: the interfacial compatibility between nano-copper and PVDF is poor, resulting in stress concentration; copper particles are oxidized to form an insulating layer (CuO), hindering ion transport; the metal filler has high rigidity and cannot buffer volume changes, leading to crack initiation.
[0128] The negative electrode buffer layers in Example 1 and Comparative Example 1 were respectively assembled into solid-state batteries according to the battery structure in Example 4. A scanning electron microscope was used to test the scanning electron micrograph of the cross-section of the battery assembled with the negative electrode buffer layer of Example 1 before cycling, as specifically shown in Figure 2 shown. Then, a scanning electron microscope was used to test the scanning electron micrographs of the battery assembled with the negative electrode buffer layer of Example 1 after 1000 cycles and the battery assembled with the negative electrode buffer layer of Comparative Example 1 after 200 cycles, as specifically shown in Figure 3 and Figure 4 shown. Among them, the cycling conditions of the battery were: cycling at a charge-discharge rate of 0.5C and a voltage range of 2.5 - 4.2V. As can be seen from Figures 2 to 4 this, there are no cracks on the surface of the battery assembled with the negative electrode buffer layer of Example 1 before cycling and after 1000 cycles, while there are obvious pores on the surface of the battery assembled with the negative electrode buffer layer of Comparative Example 1 after 200 cycles, further indicating that the interfacial contact of the negative electrode buffer layer of Comparative Example 1 is poor and it is prone to falling off during cycling.
[0129] The above has described the embodiments of the present invention in detail. However, the present invention is not limited to the above embodiments, and various changes can be made without departing from the spirit of the present invention within the scope of knowledge possessed by those of ordinary skill in the art. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A negative electrode buffer layer, characterized in that: It includes a base material with a mass percentage of 60 to 80% and a functional filler with a mass percentage of 20 to 40%; The base material includes a polymer; The functional filler includes at least one of an inorganic ion conductor, a conductive carbon material, and a nano-oxide.
2. The negative electrode buffer layer according to claim 1, wherein: The polymer has at least one of the following characteristics: (a1) The polymer includes at least one of polyvinylidene fluoride, polyethylene oxide, polyurethane, and polyacrylonitrile; (a2) The elastic modulus of the polymer is 0.1 to 2 GPa; (a3) The elongation at break of the polymer is ≥ 300%; (a4) The weight-average molecular weight of the polymer is 50,000 to 1.2 million.
3. The negative electrode buffer layer according to claim 1, characterized in that: The inorganic ion conductor includes at least one of lithium lanthanum zirconium oxide, lithium titanium oxide, Li3PS4, lithium germanium phosphorus sulfide compound, lithium aluminum titanium phosphate, and lithium aluminum germanium phosphate; And / or, the conductive carbon material is selected from at least one of graphene, carbon nanotubes, acetylene black, carbon fiber, carbon black, graphite, carbon aerogel, and carbon quantum dots; And / or, the nano-oxide is selected from at least one of nano-Al2O3, nano-ZrO2, nano-titanium dioxide, nano-zinc oxide, nano-iron oxide, and nano-silica.
4. The negative electrode buffer layer according to claim 1, wherein: The functional filler has at least one of the following characteristics: (b1) The particle size of the functional filler is ≤ 1 μm; (b2) The conductivity of the functional filler ≥ 1×10 -4 S / cm; (b3) The specific surface area of the functional filler ≥ 10 m 2 / g.
5. The negative electrode buffer layer according to any one of claims 1 to 4, characterized in that: The polymer and the functional filler are connected by at least one selected from physical entanglement, chemical bond, and π-π interaction.
6. The negative electrode buffer layer according to any one of claims 1 to 4, characterized in that: The thickness of the negative electrode buffer layer is 1 to 10 μm.
7. The method for preparing the negative electrode buffer layer according to any one of claims 1 to 6, characterized in that: It includes the following steps: Making a slurry from a raw material including a base material and a functional filler, and then forming a film from the slurry to obtain the negative electrode buffer layer.
8. The method for preparing the negative electrode buffer layer according to claim 7, wherein: The slurry also contains a solvent, and the solvent includes at least one of N-methylpyrrolidone, ethanol, acetone, and isopropyl alcohol.
9. A solid-state battery, comprising a positive electrode, a solid electrolyte, and a negative electrode, characterized in that: The solid-state battery also includes the negative electrode buffer layer according to any one of claims 1 to 6; the negative electrode buffer layer is located between the negative electrode and the solid electrolyte.
10. Application of the negative electrode buffer layer according to any one of claims 1 to 6 in a battery.
Citation Information
Cited By
High-performance carbon fiber coaxial structure energy storage battery and preparation method thereof
CN120834250A